2018
DOI: 10.1186/s12974-018-1107-7
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosative damage during retrovirus infection-induced neuropathic pain

Abstract: BackgroundPeripheral neuropathy is currently the most common neurological complication in HIV-infected individuals, occurring in 35–50% of patients undergoing combination anti-retroviral therapy. Data have shown that distal symmetric polyneuropathy develops in mice by 6 weeks following infection with the LP-BM5 retrovirus mixture. Previous work from our laboratory has demonstrated that glial cells modulate antiviral T-cell effector responses through the programmed death (PD)-1: PD-L1 pathway, thereby limiting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 82 publications
1
13
0
Order By: Relevance
“…28 The infiltration of lymphocytes into DRG and spinal cord has been demonstrated in an LP-BM5, a murine retroviral isolate, infected murine AIDS (MAID) model. 39 Specifically, these immune cells released redox-active species into DRG neurons, resulting in oxidative damage and increased mechanosensitivity of the hindpaw. 39 The role of macrophages in neuropathic pain is further emphasized by demonstration of reduced mechanical hypersensitivity and Wallerian degeneration in rats after depletion of macrophages with dichloromethylene diphosphonate-containing liposomes.…”
Section: Peripheral Immune Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…28 The infiltration of lymphocytes into DRG and spinal cord has been demonstrated in an LP-BM5, a murine retroviral isolate, infected murine AIDS (MAID) model. 39 Specifically, these immune cells released redox-active species into DRG neurons, resulting in oxidative damage and increased mechanosensitivity of the hindpaw. 39 The role of macrophages in neuropathic pain is further emphasized by demonstration of reduced mechanical hypersensitivity and Wallerian degeneration in rats after depletion of macrophages with dichloromethylene diphosphonate-containing liposomes.…”
Section: Peripheral Immune Cellsmentioning
confidence: 99%
“…39 Specifically, these immune cells released redox-active species into DRG neurons, resulting in oxidative damage and increased mechanosensitivity of the hindpaw. 39 The role of macrophages in neuropathic pain is further emphasized by demonstration of reduced mechanical hypersensitivity and Wallerian degeneration in rats after depletion of macrophages with dichloromethylene diphosphonate-containing liposomes. 40 Other animal models limiting macrophage recruitment have also demonstrated a corresponding reduction in neuronal degeneration and hyperalgesia.…”
Section: Peripheral Immune Cellsmentioning
confidence: 99%
“…GraphPad Prism 5.0 software (GraphPad Software, Inc., La Jolla, CA, USA) was used for data analysis. 38 Two-tailed Student's t-test and a one-way analysis of variance were used to evaluate the significance of the data. Differences were considered statistically significant at P,0.05 (*) or P,0.01 (**).…”
Section: Discussionmentioning
confidence: 99%
“…In this review, we primarily discuss findings from various murine models. We have previously shown that PD-1 KO animals displayed significantly greater mechanical hypersensitivity than wild type mice during chronic murine retroviral (LP-BM5) infection, which was associated with significantly increased infiltration of T-lymphocytes, macrophages, and microglial activation [46]. In MCMV-induced brain infection there is chronic neuroinflammation, which persists within the post-encephalitic brain even in the absence of detectable viral antigen [2].…”
Section: Pd-l1: Mixed Blessings In Cns Diseasementioning
confidence: 99%